Studi Komparasi Keterampilan Menulis dan Karakteristik Teks Berita di Boarding School - Ma'ruf, Anas; Sudaryanto, Memet; Bivit Anggoro Prasetyo (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This research was motivated by the implementation of the boarding school education system. In boarding schools, there are students living in dormitories and outside dormitories. This does not deny that there will be differences in the condition of the student. No exception to the writing skills and characteristics of news texts. This study aims to determine the comparison of writing skills and news text characteristics between boarding and non-boarding students. This research is a comparative research with a qualitative descriptive approach conducted at MTs Al Ikhsan Beji, Kedungbanteng. Data collection techniques in this study used performance, documentation, and interview methods. The results showed that; (1) there are differences in the writing skills of news texts of boarding and non-boarding students; (2) the news text writing skills of boarding students are slightly better than non-boarding students; and (3) the most striking characteristic differences between boarding and non-boarding student news texts are in the selection of venues and topics. The conclusion of this study provides related suggestions when learning to write news texts, teachers should use methods that make students feel happy, and in writing news texts, teachers should also assign news text editing, so that student news text results are minimal.